Enhanced oxygen‐barrier and water‐resistance properties of poly(vinyl alcohol) blended with poly(acrylic acid) for packaging applications. Issue 4 (9th February 2016) - Lim, Mijin; Kim, Dowan; Seo, Jongchul
Abstract : Poly(vinyl alcohol) (PVA) was cross‐linked by thermal condensation with various weight ratios of poly(acrylic acid) to improve the physical properties of PVA for expanded use as a packaging materials. Abstract: To enhance the oxygen‐barrier and water‐resistance properties of poly(vinyl alcohol) (PVA) and expand its food packaging applicability, five crosslinked poly(vinyl alcohol)/poly(acrylic acid) (PVA/PAA) blend films were prepared via esterification reactions between hydroxyl groups in PVA and carboxylic acid groups in PAA. The physical characteristics of the blends, including the thermal, barrier, mechanical and optical properties, were investigated as a function of PAA ratio. With increasing PAA content, the crosslinking density was significantly increased, resulting in changes in the chemical structure, morphology and crystallinity of the films. The oxygen transmission rate of pure PVA decreased from 5.91 to 1.59 cc m −1 day −1 with increasing PAA ratio. The water resistance, too, increased remarkably. All the blend films showed good optical transparency. The physical properties of the blend films were strongly correlated with the chemical structure and morphology changes, which varied with the PAA content. © 2016 Society of Chemical Industry